Comparative Study of Dermatological Diseases of the Elderly in Relation to the Rest Population - Papadopoulos I (Dove Medical Press, 2020)
Iordanis Papadopoulos Department of Aesthetics and Cosmetology, Alexander Technological Educational Institute of Thessaloniki, Thessaloniki, GreeceCorrespondence: Iordanis Papadopoulos Email driordanis@yahoo.grBackground: According to Eurostat, the geriatric population in Greece constitutes almost 21.8% of the total population, with an increasing tendency. Skin diseases of the elderly often originate from internal medicine diseases. The aim of this study was to identify different dermatological conditions among patients over 65 years of age compared to younger patients.Methods: The present study was conducted between May 2015 and December 2017 in public medical offices in the Municipality of Thessaloniki. A total of 8422 patients of all ages were screened and their dermatological problem was recorded. The sample was then divided into two age groups. The first group was composed of 3629 elderly patients over 65 years of age. The second group consisted of 4793 patients up to 65 years old.Results: Pruritus was the main dermatological complaint in the elderly (14.2%) compared to the younger age group (1%), who were more interested in their mole examination (15.1%). Precancerous lesions (4%) and skin cancers (2.4%) presented more frequently in elderly patients than in people younger than 65 years old (0.7% and 0.5%, respectively).Conclusion: There are significant differences in the frequency and etiology of dermatological diseases between the two age groups. Pruritus and non-cancerous tumors of the elderly are considered to be the main findings of geriatric dermatology.Keywords: geriatric dermatology, skin cancer, epidemiology, pruritus, skin ageing